Exploring Minimal Pairs of Consonants in English: A Literature Review - Afifah, Nadhira; Lubis , Yani (Jurnal Pendidikan Rafflesia, 2023)
English /1/ has traditionally been classified into at least two allophones, an easier syllable that usually comes first, and dark, which is the final syllable. When he discovered the vowel /1/s that precedes the phonetic possibility of a phonetic boundary between the two extremes, most researchers eventually assumed that the phoneme's allophones were categorically distinct elements. This article introduces acoustic and X-ray microbeam data for English /1/, before and prior to the phonological boundary, associated with /i - 1/. The main light-dark contrast levels of the articulation appear as follows: (1) greater retraction and tongue drop for the darker dorsal variant of /I/; (2) earlier occurrence in the darker version of /1/ of dorsal retraction and limb drop relative to apical limb rise versus the easier time version of /1/ in which the hind limb is later than the apical limb. It can also be seen that the darkness of /1/ is with the above articulatory measures and formant frequency measures - correlating strongly with the acoustically measured duration of rhymes containing the /1/ prefix. We interpret our results as evidence that there is no reason for the treatment of light and dark allophones as phonologically distinct (or phonetic) entities in English. Instead, the phonologically singular, entity /1/ is phonetically realized as a lighter or darker variant depending on factors such as the position of /1/ in the syllable, and the phonetic duration of the prosodic context containing /I/. It is suggested that /1/s contains back vowel motion as well as consonant peak motion. It is suggested that the vowel motion has a strong affinity to the core syllable, while the consonant motion has a strong affinity to the margin. The two movements of: /1/ so basically the asynchronous sound motion comes through the previous last syllable (i.e. /1/s closest to the dot). The consonant mark, and the opposite situation remains the initial syllable /1/s. For this explanation to work, the phonetic implementation must have access to information in the syllable position of the phonological elements. We will talk about how most of the correlation is due to underdrive coarticulation with darkness duration.